PENGARUH PENGAWASAN DAN STRES KERJA TERHADAP KEPUASAN KERJA PARAMEDIS RUMAH SAKITAZ–ZAHRA KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - Agustina, Lestari Ria; Zulfadil, Zulfadil; Arwinence, Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of Supervision and Job Stress onJob Satisfaction of Paramedics at Az–Zahra Hospital, Ujungbatu District, RokanHulu Regency. The population in this study were all employees working at AzZahra Hospital Ujungbatu, totaling 78 people. In this study, the sample used was30 samples of paramedical employees. Sampling used a purposive samplingmethod. The primary data in this study were obtained through interviews anddistributing questionnaires to prove the research results. The hypothesis testing inthis study was using multiple linear analysis with the help of the SPSS program.The results showed that: 1) partial job supervision had a significant effect onparamedics' job satisfaction in hospitals, 2) partial work stress had no significanteffect on paramedics' job satisfaction in hospitals, 3) supervision and work stresshad a joint effect significant effect on paramedic job satisfaction. Keywords: Supervision, Job Stress, Job Satisfaction